2022
DOI: 10.1002/ange.202117205
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Transformation of PET and CO2 into High‐Value Chemicals

Abstract: Polyethylene terephthalate (PET) and CO2, two chemical wastes that urgently need to be transformed in the environment, are converted simultaneously in a one‐pot catalytic process through the synergistic coupling of three reactions: CO2 hydrogenation, PET methanolysis and dimethyl terephthalate (DMT) hydrogenation. More interestingly, the chemical equilibria of both reactions were shifted forward due to a revealed dual‐promotion effect, leading to significantly enhanced PET depolymerization. The overall methano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Li et al demonstrated a transformation that utilized PET, CO 2 , and H 2 to produce a dicarboxylated cyclohexane derivative (Figure 6). 157 Tanaka et al instead captured EG with dimethyl carbonate, which led to good yields of DMT (72−91%) and ethylene carbonate (69−86%) at 65 °C. 158 Mild methanolysis conditions have been reported with respectable yields of DMT (71−86%) attainable at 70 °C using MeOK, K 2 CO 3 , or TBD as catalyst.…”
Section: Methanolysismentioning
confidence: 99%
See 2 more Smart Citations
“…Li et al demonstrated a transformation that utilized PET, CO 2 , and H 2 to produce a dicarboxylated cyclohexane derivative (Figure 6). 157 Tanaka et al instead captured EG with dimethyl carbonate, which led to good yields of DMT (72−91%) and ethylene carbonate (69−86%) at 65 °C. 158 Mild methanolysis conditions have been reported with respectable yields of DMT (71−86%) attainable at 70 °C using MeOK, K 2 CO 3 , or TBD as catalyst.…”
Section: Methanolysismentioning
confidence: 99%
“…Li et al demonstrated a transformation that utilized PET, CO 2 , and H 2 to produce a dicarboxylated cyclohexane derivative (Figure ). Tanaka et al. instead captured EG with dimethyl carbonate, which led to good yields of DMT (72–91%) and ethylene carbonate (69–86%) at 65 °C .…”
Section: Poly(ethylene Terephthalate)mentioning
confidence: 99%
See 1 more Smart Citation
“…As an example of the selective conversion of PLA into alanine, 75 commercial PLA was directly utilized as a feedstock for alanine generation with the aid of ammonium hydroxide that served as the agent for both depolymerization and nitrogen source for PLA upgrading. In another case, the conversion of primary PET into value‐added chemicals (e.g., dimethyl cyclohexanedicarboxylates [DMCD]) was developed 135 . During this process, the PET depolymerization was investigated in the presence of methanol, and the obtained product (i.e., dimethyl terephthalate) could be utilized as feedstock for hydrogenation, generating high‐value chemicals (i.e., DMCD).…”
Section: Photocatalytic Plastic Conversionmentioning
confidence: 99%
“…In another case, the conversion of primary PET into value-added chemicals (e.g., dimethyl cyclohexanedicarboxylates [DMCD]) was developed. 135 During this process, the PET depolymerization was investigated in the presence of methanol, and the obtained product (i.e., dimethyl terephthalate) could be utilized as feedstock for hydrogenation, generating high-value chemicals (i.e., DMCD). The forementioned studies have paved a new avenue for plastic upgrading, in which plastic wastes could be converted into valuable substances.…”
Section: Selective Photooxidation Of Plasticmentioning
confidence: 99%